Base-Hurricane: A new extension for the Landis-II forest landscape model. (November 2020) - Schrum, Paul; Scheller, Robert M.; Duveneck, Matthew J.; Lucash, Melissa S.
Abstract: Hurricanes in the southeast United States are infrequent disturbances that affect large areas and have a large effect on forest succession. In order to understand and quantify this effect, we added a new module to the LANDIS-II landscape change model. Focusing on the southeast coast of the United States, we simulated stochastic hurricanes for 50 years. For each simulated storm, the new model extension generates the maximum sustained wind speed over the region and uses the resulting parameter surface to compute maximum sustained wind speed for each cohort cell in a raster grid. Mortality is estimated for each species and age cohort in each cell based on the maximum sustained wind speed, altering forest succession. Results indicate that hurricanes reduce average aboveground biomass by > 20% over 50 years on a landscape in Fort Bragg, North Carolina (USA) compared to a scenario without hurricanes and increased uncertainty of projected succession. Highlights: Hurricanes are a significant source of mortality to forests in the southeast United States. We developed a new LANDIS-II extension to model disturbance caused by hurricanes. Hurricanes reduce aboveground biomass at regional scales compared to localized disturbances such as harvesting or fire. Total above ground biomass is reduced by hurricanes at longer time scales. Hurricanes favor angiosperms although the overall effect was minor within our test landscape.